Portrayal of Modern Life: A Reading on Margaret Laurence’s the Fire Dwellers - Ebinezer, D. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Stacey the protagonist in Fire Dwellers longed to be a modern woman. Tradition did not appeal much to her. Beyond her sufferings she wanted to telecast herself as a modern lady. From her life, it was understood that her family life was not what she expected and future remained understandable. She felt solace by pretending herself to be a modern lady. The sufferings, conflicts, bitter experiences, are clearly pictured in the novel. The paper presents a general note on modern life and through the influence of modernity Stacey, the major character created by Margaret Laurence.
Keywords: Criticism; literature; literary theory; Margaret